2018
DOI: 10.1097/j.pain.0000000000001319
|View full text |Cite
|
Sign up to set email alerts
|

Chronic itch impairs mood and HPA axis function in mice: modulation by CRFR1 antagonist

Abstract: Chronic itch is clinically correlated with the development of mood disorders such as anxiety and depression. Nonetheless, whether this relevance exists in rodents is unknown, and evidence demonstrating chronic itch can affect mood is lacking. The aim of this study is to characterize the affective consequences of chronic itch, and explore potential mechanisms and interventional strategy. We subjected mice to chronic itch by repetitive cutaneous treatment with acetone and diethylether followed by water (AEW) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This was confirmed also by other single center studies (Stumpf et al, 2018). A speculative reason for this correlation is that itch correlates with skin inflammation and skin inflammation induces the serotonin network in the brain, leading to depression and anxiety (Yosipovitch et al, 2008;Zhao et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…This was confirmed also by other single center studies (Stumpf et al, 2018). A speculative reason for this correlation is that itch correlates with skin inflammation and skin inflammation induces the serotonin network in the brain, leading to depression and anxiety (Yosipovitch et al, 2008;Zhao et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…The psychological burden produced by chronic itch was reported with high incidences of suicidal motivation (21.1%) and psychiatric illnesses (70%) ( 93 ). Zhao et al ( 94 ) reported that AEW mice developed anxiety-like symptoms 2–3 weeks and depression-like phenotypes 3–4 weeks after AEW treatment, suggesting that mood impairment due to chronic itch evolves over time. The mood impairment behaviours were significantly related to the itch-associated behaviour.…”
Section: Itch Of Dry Skin and Anxietymentioning
confidence: 99%
“…Other studies have confirmed this ( 36 ). One presumed reason for this correlation is that itching is associated with skin inflammation, which induces serotonin networks in the brain, leading to depression and anxiety ( 37 , 38 ). Therefore, the symptoms of itching can be used as a major cause of mediating the occurrence of anxiety and depression in patients with CSU.…”
Section: Discussionmentioning
confidence: 99%